Mitsuokella jalaludinii sp. nov., from the rumens of cattle in Malaysia - Lan, G. Q.; Ho, Y. W.; Abdullah, N. (Microbiology Society, 2002)
Five strains of phytase-producing, gram-negative, non-spore-forming, non-motile, small, stout, rod-shaped, strictly anaerobic, fermentative bacteria were isolated from the rumens of cattle in Malaysia. All five strains had morphological, physiological and biochemical features in common. Although these strains had many physiological and biochemical characteristics that were identical to those of the Mitsuokella multacida type strain (ATCC 27723T), they could be distinguished from this species by means of the following characteristics: a smaller cell size (1.2-2.4 microm long and 0.6-0.8 microm wide); a lower final pH value (3.8-4.0) in peptone/yeast extract/glucose broth; inhibition by 0.001% brilliant green; insensitivity to kanamycin (100 microg ml(-1)) and penicillin (10 microg ml(-1)); a higher optimum growth temperature (approx. 42 degrees C); the ability to grow at 45 and 47 degrees C; the ability to ferment glycerol, sorbitol and amidon; and the inability to ferment mannitol, rhamnose, D-tagatose and melezitose. The G+C content of the type strain (M 9T) of these five strains was 56.9 mol%. Analysis of the 16S rRNA gene sequence of type strain M 9T indicated that the strain falls within the genus Mitsuokella. The sequence similarity between type strain M 9T and Mitsuokella multacida was 98.7%. The DNA-DNA relatedness between type strain M 9T and Mitsuokella multacida type strain DSM 20544T (= ATCC 27723T) was 63.8%, indicating that, in spite of a high level of similarity for the 16S rRNA gene sequence, type strain M 9T is independent of Mitsuokella multacida at the species level. On the basis of these results, a new species, Mitsuokella jalaludinii sp. nov., is proposed for these strains. The type strain is M 9T (= DSM 13811T = ATCC BAA-307T).